(untitled) (Global Journal of Human-Social Science, 2023)
To discuss the main aspects of the therapeutic-occupational process of a young polytraumatized patient during his hospitalization and to reflect on the clinical reasoning of occupational therapists under the theoretical framework of the Dynamic Occupational Therapy Method This is a case report of a victim of multiple trauma A review of the clinical evolution of the team was performed followed by the description of occupational therapy visits and analysis of the therapeutic process The subject who suffers a sudden illness has his daily life interrupted by the need for immediate and generally prolonged hospitalization Dynamic occupational therapy aims to promote the construction of a new routine through its techniques centered on the triadic relationship This relationship was discussed in three categories communication carrying out activities and addressing palliative care Urgent and emergency hospitals are fields in growing expansion for occupational therapy however the performance of this professional in this context is still a little explored subject in Brazil and in the world To discuss the main aspects of the therapeutic-occupational process of a young polytraumatized patient during his hospitalization and to reflect on the clinical reasoning of occupational therapists under the theoretical framework of the Dynamic Occupational Therapy Method This is a case report of a victim of multiple trauma A review of the clinical evolution of the team was performed followed by the description of occupational therapy visits and analysis of the therapeutic process The subject who suffers a sudden illness has his daily life interrupted by the need for immediate and generally prolonged hospitalization Dynamic occupational therapy aims to promote the construction of a new routine through its techniques centered on the triadic relationship This relationship was discussed in three categories communication carrying out activities and addressing palliative care Urgent and emergency hospitals are fields in growing expansion for occupational therapy however the performance of this professional in this context is still a little explored subject in Brazil and in the world